Answer:
Multiply x + y = 3 by 3 and add it to -3x - 2y = -7
Step-by-step explanation:
When using elimination to solve a system of equations, you multiply one equation by some number. The reason for doing this is that when you add it to the second equation, you want one variable to cancel out. When one variable cancels out (in this case x), you can solve for the other variable (in this case y). I will show this:
3(x + y = 3) = 3x + 3y = 9
3x + 3y = 9
+ -3x + -2y = -7
---------------------------
y = 2
Now, knowing that y = 2, you can substitute y=2 into either equation to solve for x.
-3x - 2(2) = -7
-3x -4 = -7
-3x = -3
x = 1 | to double check (1, 2) as your answer plug these values into both equations
Finding this solution would not have been possible if not for cancelling out the x's above. The other three are wrong because none of the other options cancels out one of the variables.
Answer:
The common difference is 3
Step-by-step explanation:
we know that
In an <u>Arithmetic Sequence</u> the difference between one term and the next is a constant called the common difference
we have
![5,8,11,14](https://tex.z-dn.net/?f=5%2C8%2C11%2C14)
so
![a1=5](https://tex.z-dn.net/?f=a1%3D5)
![a2=8](https://tex.z-dn.net/?f=a2%3D8)
![a3=11](https://tex.z-dn.net/?f=a3%3D11)
![a4=14](https://tex.z-dn.net/?f=a4%3D14)
![a2-a1=8-5=3](https://tex.z-dn.net/?f=a2-a1%3D8-5%3D3)
![a3-a2=11-8=3](https://tex.z-dn.net/?f=a3-a2%3D11-8%3D3)
![a4-a3=14-11=3](https://tex.z-dn.net/?f=a4-a3%3D14-11%3D3)
therefore
The common difference is 3
Answer:
The first option.
Step-by-step explanation:
Answer:
0.75 is it the answer
Step-by-step explanation: